Muslims’ Poetry Up Until End of the Umayyad Era Between Virtual "Muslimism" & Enforced Reality - Ahmad, Adnan (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The poetry of Early Islam and the Umayyad Era has been influenced by the new religion, but it has not been an "Islamic" poetry in the full sense of the word. Had the expectation of the emergence of an "Islamic" poetry in Early Islam a matter of excessive optimism, due to the short period, excessive events, and people’s juvenile cognizance of the new religion, then there has existed in the era of the Umayyad State, its stability, and breadth of its poetical production, what exegetises the absence of such poetry. This piece of research is a mere attempt to scrutinize those reasons; however, it hypothesizes that such a question would not materialise except through unveiling the great factors that influence the Umayyad artistic taste—since it stands as the force that stimulates creativity, or greatly contributes to its orientation, because it controls the creator and the receptor altogether